Brazil Financial Intermediation Costs and Credit Allocation - Pazarbasioglu-Dutz, Ceyla (World Bank, Washington, DC, 2017)
Earmarked credit was about half of total credit in Brazil at end-2015, after declining to one third of total credit in 2007, it is back to the levels in late 1990s. During 2008-15, earmarked credit increased from 12 to close to 30 percent of GDP. Initially, the objective was to counteract the retrenchment in lending by private lenders. However, earmarked credit expansion continued during the subsequent commodity boom period. This paper provides a taxonomy of the complex earmarked credit system and a preliminary analysis of the potential implications. The interventions include a complex web of price and quantity regulations, reserve requirements, tax exemptions and forced savings schemes that are used for earmarked lending to specific sectors. The objective of the taxonomy is to understand who funds the system, who benefits from it and how is it intermediated.